Vulnerability of Demersal Fish Assemblages to Trawling Activities: A Traits-Based Index - de Juan, Silvia; Hinz, Hilmar; Sartor, Paolo; Vitale, Sergio; Bentes, Luis; Bellido, Jose M.; Musumeci, Claudia; Massi, Daniela; Gancitano, Vita; Demestre, Montserrat (Frontiers in Marine Science, 2020)
Reducing the impact on vulnerable species through changes in fishing practices, such as the spatial or temporal avoidance of certain areas, is key to increase the ecological sustainability of fisheries. However, it is often hampered by the availability of sufficiently detailed data and robust indicators. Existing trawl surveys are a cost-effective data source to assess the vulnerability of fishing areas based on the quantities of vulnerable species caught. We developed a biological traits-based approach to the vulnerability of demersal assemblages using commercial trawl catch data. An expert-based approach identified a set of biological traits that are expected to condition the species’ response to trawling impact and are combined to produce the vulnerability index ranked into four levels (low, moderate, high and very high vulnerability). The approach was tested in four southern European fishing grounds showing evidence of over-exploitation, through catches being dominated by species of relatively low vulnerability to fishing impacts. The general distribution of species’ biomass amongst vulnerability groups was highly homogenous across case studies, despite local differences in fishing fleet structure, target species and fishing depths. Within all areas the species with moderate vulnerability dominated and, in most instances, species of “very high” vulnerability were not recorded. Nevertheless, differences emerged when comparing the proportions of highly vulnerable species in the catches. Variability in vulnerability level of the catch was also observed at small spatial scales, which was principally explained by differences in habitat type and depth and, secondarily, by fishing effort. In fine mud in the shallower areas there was a higher presence of low vulnerable fauna. Furthermore, vulnerable organisms decreased in their presence in sandier substrates on the continental shelf. The spatial heterogeneity in assemblage vulnerability composition encourages the potential for adoption of this index in the spatial management of fishing grounds aiming at ensuring a sustainable exploitation by mitigating trawl impacts on the most vulnerable components of the demersal assemblages.